Mouse's first night at Moonlight School (Nosy Crow, 2014)
A gentle, reassuring tale which is perfect for all little ones who are about to start school. It's Mouse's first day at Miss Moon's Moonlight School for all the small creatures of the night. But Mouse is VERY shy, too shy to even say hello. Luckily, with help from Miss Moon and her new friends Bat, Cat and Owl, a game of hide-and-seek makes Mouse feel right at home. Ages 3-5